Conference Scene: From innovative polymers to advanced nanomedicine: key challenges, recent progress and future perspectives. (February 2013) - Feijen, Jan; Hennink, Wim E; Zhong, Zhiyuan
Recent developments in polymer-based controlled delivery systems have made a significant clinical impact. The second Symposium on Innovative Polymers for Controlled Delivery (SIPCD) was held in Suzhou, China to address the key challenges and provide up-to-date progress and future perspectives in the innovation of polymer-based therapeutics. At SIPCD, a stimulating panel discussion was introduced for the first time on "What is the future of nanomedicine?" This report highlights the most recent research and developments in biomedical polymers and nanomedicine made by 29 invited scientists from around the world, as well as important issues regarding clinical advancements of nanomedicine conferred during the panel discussion.